Personality and Parkinson's disease: A meta-analysis. (April 2018) - Santangelo, Gabriella; Garramone, Federica; Baiano, Chiara; D'Iorio, Alfonsina; Piscopo, Fausta; Raimo, Simona; Vitale, Carmine
Abstract: Introduction: Personality changes are considered pre-motor features of Parkinson's disease (PD). Cross-sectional studies revealed that PD patients were more introvert, apprehensive, and cautious than healthy subjects (HS), whereas other studies failed to disclose these behavioural traits. Some studies found mixed results concerning Novelty Seeking (NS) and Harm Avoidance (HA) profiles in PD patients. To better clarify the personality profile in PD we performed a meta-analysis on studies exploring such topic according to both Cloninger's Psychobiological Model (PM) and Big Five Model (BFM) Methods: The meta-analysis included 17 studies evaluating the personality in PD patients compared with HS. The outcomes were the dimensions of the temperament and character of the PM and personality traits of BFM. Effect sizes from data reported in the primary studies were computed using Hedges'g unbiased approach. Heterogeneity among the studies and publication bias were assessed. Meta-regressions were conducted with age at evaluation, gender, schooling, and type of personality trait tools as moderators. Results: As for PM, PD patients scored higher on HA and lower on NS than HS. No difference was found on Reward Dependence, Perseverance/Persistence and on character level. As for BFM, higher levels of Neuroticism, but lower levels of Openness and Extraversion were associated with PD. Discussion: The personality profile in PD is characterized by high Neuroticism and HA, and by low Openness, Extraversion and NS. The personality profile delineated in the present study on PD patients seems to reflect the premorbid one and might contribute to development and persistence of affective disorders. Highlights: Personality changes are considered non-motor features of Parkinson's disease (PD). The personality profile in PD is characterized by higher Neuroticism/Harm Avoidance. Openness, Novelty Seeking and Extraversion are inversely associated with PD. The meta-analysis delineated a personality profile associated with PD, which may occur in the pre-motor stages.